Pengaruh Crowding Out Pengeluaran Tembakau terhadap Konsumsi Rumah Tangga di Sumatra Barat - Akbar, Urmatul Uska; Sari, Yollit Permata; Marta, Joan; Satria, Doni; Adry, Melti Roza; Putri, Dewi Zaini; Yeni, Isra (Jurnal Ekonomi dan Pembangunan Indonesia, 2022)
Crowding out analysis emphasizes the extent to which household spending on tobacco affects other baskets of household expenditures. The data used in this study is the National Socio-Economic Survey in 2016. Using the Quadratic Almost Ideal Demand System equation, this study found that tobacco expenditure has a negative and significant effect on almost all types of household expenditures, such as fuel, education, entertainment, clothing, health, and durable goods. Household durable goods expenditure is the most displaced or sacrificed, followed by education expenditure. This finding reveals tobacco consumption has effect on human capital investment and long-run economic growth in West Sumatra.